2019
DOI: 10.1016/j.celrep.2019.11.077
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Epigenome, Exome, and Transcriptome Analyses Reveal Molecular Subtypes and Homeotic Transformation in Uterine Fibroids

Abstract: Highlights d Epigenetic and gene expression profiles define molecular subtypes of uterine fibroids d DNA hypomethylation in the HMGA2 gene body is consistent with activation of the gene d HOXA gene cluster expression displays a more posterior pattern in uterine fibroids d Homeotic transformation appears to play a role in fibroid biology

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 107 publications
(100 reference statements)
5
64
0
Order By: Relevance
“…Two samples, originally classified as HMGA1 overexpressing leiomyomas [ 14 ], displayed clear expression patterns of leiomyomas of the FH subtype. Exome sequencing revealed a somatic missense variant FH c.955G > A, p.(Asp319Asn) and a somatic intronic variant FH c.556-24T > G in one of the samples (MP169F, Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two samples, originally classified as HMGA1 overexpressing leiomyomas [ 14 ], displayed clear expression patterns of leiomyomas of the FH subtype. Exome sequencing revealed a somatic missense variant FH c.955G > A, p.(Asp319Asn) and a somatic intronic variant FH c.556-24T > G in one of the samples (MP169F, Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have also revealed that the majority of leiomyomas can be classified into three main molecular subtypes, reflecting mutations in MED12 , HMGA2 , and FH . Furthermore, we and others have shown that each subtype is characterized by a distinct global gene expression pattern [ 7 , 14 ], suggesting that leiomyomas could be classified by gene expression profiling. However, RNA-based studies on leiomyomas have largely been limited to fresh frozen tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations